The Influence of Compensation and Work Discipline on Employee Performance: A Case Study of Employees at the Muhammadiyah Zakat Management Organization (LAZISMU) - Eri Adinata, Restu; Khikmatun, Rizka; Wuryani, Eni (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
The Muhammadiyah Amil Zakat Organization (LAZISMU) stands as a beacon among Indonesia's official zakat bodies, dedicated to the noble task of gathering and disbursing zakat, infaq, and sadaqah (ZIS) from the generous hearts of the community. Within its halls, LAZISMU employees are the artisans shaping the destiny of their organization, tasked not only with collecting funds but also with igniting flames of hope through empowerment initiatives, thereby kindling the welfare of society. In the verdant landscapes of East Java, a study unfolds, seeking to unravel the intricate dance between compensation, work discipline, and the performance of LAZISMU employees. Surveying fifty dedicated souls, the study's findings unveil intriguing truths. Compensation, it seems, holds no sway over the performance of these diligent stewards of charity. Yet, amidst this revelation, a beacon of hope emerges: the torchbearer of work discipline. Here lies the key, for as discipline tightens its grip, so does the flame of performance blaze brighter. It is a testament to the power of dedication, the fuel that propels LAZISMU forward on its noble quest to uplift the community it serves.